GREEN ECONOMY: RECONCEPTION OF ISLAMIC ECONOMIC'S JUSTICE PRINCIPLE - Ni'matul Ulya, Husna (Sekolah Tinggi Agama Islam Nahdlatul Ulama Madiun, 2022)
Changes and environmental damage due to economic activity in an economic system that impacts the scarcity of natural resources give rise to a new concept of a green economic system that continues the concept of sustainable development. The green economy can be understood by one keyword of justice for inter and intra-generation. In Islamic economics, this concept already existed before the thought of sustainable development in 1987 and green economy in 1989. This research aims to analyse and compare the concept of justice from the green economy and Islamic economics perspective using a qualitative approach in literature research from various secondary sources (books, articles, rules, and internet data). This study shows a relationship in the concept of value or the principle of justice in the green economy or Islamic economics conception. The equation lies in how the goal will be achieved. The difference in conception between the two lies on which the two systems are based and the epistemology of both. Green economics is rooted in the development of western economics, starting from Adam Smith and followed by other western economic scientists. In contrast, Islamic economics is based on the Qur'an and Hadith. The community’s welfare is determined by economic activities that maintain justice for inter and intra-generation in all fields. Keywords: green economy, sustainable development, justice, Islamic economy